2015
DOI: 10.1186/s40064-015-1102-8
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the microvascular circulation in the leg muscles, pancreas and small intestine in rats

Abstract: To study the microvascular circulation, we examined the proportion of open and functioning capillaries in the leg muscles, pancreas and small intestine of anesthetized rats. Fluorescein isothiocyanate (FITC)-labeled Lycopersicon esculentum lectin was injected into the heart and allowed to circulate for 3 min to label open and functioning capillaries. Specimens were removed, frozen, sectioned and double-immunostained. Using one section, open and functioning capillaries were detected by immunostaining for this l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 33 publications
(62 reference statements)
1
3
0
Order By: Relevance
“…RBC flux is present in most capillaries at rest and increases with exercise to meet the muscle demand [41]. In agreement with this, Maeda et al [42] reported that the number of capillaries exchanging oxygen was 93.0 + 5.5% of all blood-perfused capillaries in rat soleus muscle. A higher difference in these numbers was found by Fraser et al [43] in rat extensor digitorum longus muscle (EDL), i.e.…”
Section: Assessment Of Microvascular Oxygen Exchange Capabilitysupporting
confidence: 69%
“…RBC flux is present in most capillaries at rest and increases with exercise to meet the muscle demand [41]. In agreement with this, Maeda et al [42] reported that the number of capillaries exchanging oxygen was 93.0 + 5.5% of all blood-perfused capillaries in rat soleus muscle. A higher difference in these numbers was found by Fraser et al [43] in rat extensor digitorum longus muscle (EDL), i.e.…”
Section: Assessment Of Microvascular Oxygen Exchange Capabilitysupporting
confidence: 69%
“…However, after imaging, most of the blood vessels observed were microvessels, and almost no large vessels were found in the data blocks included in the analysis. This limitation might be related to the staining characteristics of lycopersicon esculentum lectin, which primarily labels the endothelium of small vessels in microvascular beds ( Porter et al, 1990 ), and marks only a few larger vessels ( Robertson et al, 2015 ), thus is often used for microvessel staining to observe and evaluate the microvascular system ( Xu et al, 2004 ; Benton et al, 2008 ; Maeda et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…The sections were incubated with the streptavidin‐biotin complex (dilution 1:50; Elite ABC; Vector). Immunoreactivity was detected by ImmPACT DAB (SK‐4105; Vector) (Maeda et al ., 2014; Maeda et al ., 2015). The sections were observed, and images were obtained using NanoZoomer S60 (Hamamatsu Photonics, Hamamatsu, Japan).…”
Section: Methodsmentioning
confidence: 99%